1983
DOI: 10.1002/clc.4960060809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium antagonists on cardiac performance in patients with dilatative cardiomyopathy evaluated by noninvasive methods

Abstract: Summary:We present 14 patients with dilatative cardiomyopathy, proven by hemodynamic and angiographic assessment who received in a single-blind, randomized study, equipotent doses of the three calcium blockers: verapamil (0.1 mg/kg i.v., followed by an infusion of 0.01 mg/kg/min), nifedipin (20 mg sublingually), or diltiazem (0.2 mg/kg i.v., followed by infusion of 0.02 mg/kg/min). Before and after treatment in 8 patients systolic time intervals were recorded with an AVLMyocard-Check (Q-S,, pre-ejection period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Maurer et al reported radionuclide ventriculographic data on six patients with dilated cardiomyopathy given an intravenous bolus of diltiazem (200 jig/kg) followed by a continuous infusion (20 jig/kg/min). 9 The left ventricular ejection fraction at rest was 0-32 (0-16) off and 0 35 (0-19) on diltiazem. Walsh et al used a similar intravenous protocol followed by a one day oral dose and reported the haemodynamic findings after invasive studies in eight patients with a mean baseline contrast ventriculographic ejection fraction of 0-24 (range 0 11-032).10 Intravenous diltiazem increased the mean stroke volume index of the group by 50%, reduced systemic vascular resistance.by 34%, and reduced pulmonary artery wedge pressure by 34% without altering the maximal first derivative of left ventricular pressure (dP/dtmax).…”
Section: Resultsmentioning
confidence: 95%
“…Maurer et al reported radionuclide ventriculographic data on six patients with dilated cardiomyopathy given an intravenous bolus of diltiazem (200 jig/kg) followed by a continuous infusion (20 jig/kg/min). 9 The left ventricular ejection fraction at rest was 0-32 (0-16) off and 0 35 (0-19) on diltiazem. Walsh et al used a similar intravenous protocol followed by a one day oral dose and reported the haemodynamic findings after invasive studies in eight patients with a mean baseline contrast ventriculographic ejection fraction of 0-24 (range 0 11-032).10 Intravenous diltiazem increased the mean stroke volume index of the group by 50%, reduced systemic vascular resistance.by 34%, and reduced pulmonary artery wedge pressure by 34% without altering the maximal first derivative of left ventricular pressure (dP/dtmax).…”
Section: Resultsmentioning
confidence: 95%